Scoring System Otomatis Pada Lomba Menembak Dengan Target Sillhouette Hewan Menggunakan Metode Klasifikasi Naive Bayes - Muhamad Taufiq Firmansyah; Rizal Maulana; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Shooting is a competitive sport that tests proficiency, accuracy and speed by using different types of weapons such as firearms to wind weapons. Shooting competitions are usually held by the Indonesian Shooter Union or PERBAKIN as a form of training and gathering of its members. In this competitions, the score calculation system still using manual method. In this research will be made â€œAutomatic Scoring System On Shooting Competition With Target Animals Sillhouette Using the Naive Bayes Classification Methodâ€ to determine which type of Sillhouette is shot and add a score on the system monitor.The Naive Bayes Classification Method is used in the classification process of the hit Sillhouette to influence the score in the Competition. The prototypes of this system use some components of ADXL335 Accelerometer, Load Cell, Limit Switch, Switch, HX711 Module, and Arduino Mega 2560 and Arduino Uno as processors. Based on the results of the test on this system, the accuracy level of the sensor data is 95.73% and the accuracy of the Naive Bayes classification is 100%.